2013
DOI: 10.4315/0362-028x.jfp-12-539
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Handling Conditions Affect Internalization of Salmonella in Baby Spinach during Washing

Abstract: Internalization of foodborne pathogens in fruits and vegetables is an increasing safety concern. The aim of this research was to assess the potential for internalization of an enteric pathogen (Salmonella enterica serotype Typhimurium) in a leafy vegetable (baby spinach) during washing as influenced by three postharvest handling conditions: (i) illumination, (ii) negative temperature differential, and (iii) relative humidity (RH). To compare these potential postharvest handling conditions, leaves were exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
(35 reference statements)
0
14
0
Order By: Relevance
“…In the field, 42 contaminated water, dust containing manures, wildlife animals, and insects can potentially serve 43 as the sources of produce contamination (Berger et al, 2010;Brandl, 2006;Cooley et al, 2014;44 Strawn et al, 2013). At the postharvest level, produce contamination may result from water used for washing and processing produce, workers, or cross-contamination from other food (Beuchat and Ryu, 1997;Gomez-Lopez et al, 2013;Lynch et al, 2009). Additionally, inadequate storage temperature (Alegre et al, 2010;Sim et al, 2013) or minimally processed vegetables such as precut vegetables may facilitate amplification of pathogens on produce (Brandl, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the field, 42 contaminated water, dust containing manures, wildlife animals, and insects can potentially serve 43 as the sources of produce contamination (Berger et al, 2010;Brandl, 2006;Cooley et al, 2014;44 Strawn et al, 2013). At the postharvest level, produce contamination may result from water used for washing and processing produce, workers, or cross-contamination from other food (Beuchat and Ryu, 1997;Gomez-Lopez et al, 2013;Lynch et al, 2009). Additionally, inadequate storage temperature (Alegre et al, 2010;Sim et al, 2013) or minimally processed vegetables such as precut vegetables may facilitate amplification of pathogens on produce (Brandl, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Research has speculated that the low bacteria recovery from food matrixes may be attributed to the strong binding affinity between the bacterial cells and the produce and the internalization of bacteria into plant tissue (16,18,25). Therefore, there is increased need to develop an effective separation strategy so that the levels of bacterial contamination are not underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that exposure of leafy greens to low relative humidity (RH) conditions before washing decreased internalization of Salmonella spp. compared to internalization in baby spinach exposed to high RH (Gomez-Lopez et al, 2013). The effect of cooling on the persistence of human Norovirus GGIi on iceberg lettuce was studied by Mormann et al (2010): neither viral capsid integrity nor genome copy number was significantly reduced by storage at 6ºC for 2 days.…”
Section: Description Of Processing Methods For Leafy Greensmentioning
confidence: 99%
“…These studies illustrate the potential of PAA and NaOCl in reducing the likelihood of cross-contamination during the washing process and establishing a minor reduction of MNV-1, as a surrogate virus for human Norovirus, present on leafy greens. Additionally, if the wash water contains pathogens, they may be internalised in the tissues (Gomez-Lopez et al, 2013). Although many studies have assessed the ability of crops to internalize human bacterial pathogens such as Salmonella through root uptake (Hirneisen et al, 2012), internalisation at the wounded tissue of fresh-cut leafy greens during washing steps in processing has not been extensively studied.…”
Section: Water Sources (Washing)mentioning
confidence: 99%
See 1 more Smart Citation